The Impact Of Job Characteristics On Employee Turnover Intention Through Psychological Contract In The Pharmaceutical Industry Of Pakistan - Sami, Abdul Ahad; Iqbal, Dr Asif (Migration Letters, 2024)
Introduction: The purpose of this research work is to examine the effect of job characteristics on intended turnover in the pharmaceutical industry of Pakistan with the ‘Psychological contract’ as a mediator amidst specialized knowledge that is pertinent to the sector’s growth. The characteristics included in this paper are autonomy, task identity, and skill variety, whereby studies were done to determine the effects of these characteristics on employee turnover intentions. Thus, the psychological contract acts as a pivotal link to breach, thereby increasing dissatisfaction and emergence of turnover. Objective: The study aims at establishing correlation between job content and turnover intention, Leader Member Exchange (LMX) as the moderator and psychological contract as mediator. Therefore, this research aims at filling this knowledge gap in relation to strategies of employee retention within the pharmaceutical industry of Pakistan and the way through which workforce stability could be boosted. Methods: The quantitative method was adopted, and based on the PLS-SEM technique to assess the hypothesis regarding the interaction[1] of job characteristics, psychological contract, LMX and turnover intention. The data were collected form 328 full time employees of pharmaceutical industries established in Pakistan. Recording of overall fit indices also supported these results. Results: The results show that among the job characteristics, autonomy was statistically significant and positive with β = 0. 058 and p < 0. 05 with corresponding tests showing significance for the-job skill variety (β = 0. 184, p < 0. 01) and feedback (β = 0. 166 p < 0. 01) to positively influence the psychological contract, thus translating to reduced turnover intention. LMX mitigates this relationship with high-quality LMX being particularly beneficial in enhancing the effect of the psychological contract on retention; (β = 0. 329, t < 0. 001). Conclusion: Consequently, the study shown that job characteristics should be encouraged and leader member relations should be promoted in order to minimize turnover intention in the context of Pakistan’s pharmaceutical industry. These findings are relevant to the organizational leaders who wish to enhance the retention rates of their employees and increase productivity through the effective job design and leadership practices. This is an important step in the validation of the model and has implications for the discussion on workforce stability within growing high demand sectors for application across the industries.